1973
DOI: 10.1039/f29736900559
|View full text |Cite
|
Sign up to set email alerts
|

High energy photoelectron spectroscopy of transition metal complexes. Part 2.—Metallocenes

Abstract: Metal and core electron binding energies of the metalfocenes of the first row transition metals are reported and discussed with the aid of approximate molecular orbital calculations. In all cases it is found that the metal atom is positively charged. The measured splitting of the metal 3s photoelectron peaks is interpreted in terms of spin delocalization in these molecules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
20
0

Year Published

1973
1973
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(27 citation statements)
references
References 0 publications
7
20
0
Order By: Relevance
“…On the basis of BE data for N in pyridine and pyridinium salts 18 and in agreement with the correlation reported by Hendrickson et al 19 between the 1s electron BE and the calculated nitrogen atom charges, the observed shift can be considered to be due to a reduction of the positive charge of the pyridinium ion. These results indicate that the adsorbate/adsorbent interactions are electrostatic and provoke a partial compensation of the charge of the aromatic ion.…”
Section: Xps Analyses Of the Precursor Powderssupporting
confidence: 73%
“…On the basis of BE data for N in pyridine and pyridinium salts 18 and in agreement with the correlation reported by Hendrickson et al 19 between the 1s electron BE and the calculated nitrogen atom charges, the observed shift can be considered to be due to a reduction of the positive charge of the pyridinium ion. These results indicate that the adsorbate/adsorbent interactions are electrostatic and provoke a partial compensation of the charge of the aromatic ion.…”
Section: Xps Analyses Of the Precursor Powderssupporting
confidence: 73%
“…XPS measurements of multilayer nickelocene yield binding energies of 284.6 eV for the C 1s transition and 854.6 and 871.7 eV for the Ni 2p 3/2 and 2p 1/2 transitions, respectively, in good agreement with literature values for molecular nickelocene [26]. C 1s and Ni 2p XPS data for a one monolayer fi lm show binding energies indistinguishable from those obtained for the multilayer nickelocene condensate.…”
Section: Evidence For Molecular Adsorptionsupporting
confidence: 73%
“…XPS gives a carbon 1s binding energy of 284.5 eV, similar to data from high exposures to the other surfaces and to molecular nickelocene values. 15 Adsorption of NiCp 2 on the NiO͑100͒ thin film yields different results than found for either Ag͑100͒ or Ni͑100͒ substrates. The HREEL spectra obtained from the NiO͑100͒/ Ni͑100͒ substrate exposed to 10 L of nickelocene are shown in Fig.…”
Section: Nio"100…mentioning
confidence: 96%
“…XPS measurements yield binding energies of 284.6 eV for the C 1s transition and 854.6 eV for the Ni 2p 3/2 transition, in good agreement with literature values for molecular nickelocene. 15 Figure 1͑a͒ shows the on and off specular HREEL spectra for one monolayer of NiCp 2 interacting directly with the Ag͑100͒ surface, produced by exposure to 11 L nickelocene at 135 K. The on specular spectrum shows modes at energies which are relatively unperturbed from vibrational modes observed for molecular NiCp 2 ͑Ref. 14͒ and for the multilayer spectrum of Fig.…”
Section: A Ag"100…mentioning
confidence: 99%